Hormonal and modality specific effects on males' emotion recognition ability. (September 2020) - Lausen, Adi; Broering, Christina; Penke, Lars; Schacht, Annekathrin
Highlights: Pre-registered study with extensive recording of emotion recognition accuracy and a large sample size ( N = 282). Small positive main effects of testosterone on recognition accuracy and of cortisol on response times. Testosterone was positively related to emotion recognition accuracy when cortisol levels were low, but not when cortisol levels were high. The interaction between testosterone and cortisol relates to emotion recognition accuracy and speed. Higher accuracy and faster response times for happy faces; angry expressions were better recognized from voices than faces. Abstract: Successful emotion recognition is a key component of human socio-emotional communication skills. However, little is known about the factors impacting males' accuracy in emotion recognition tasks. This pre-registered study examined potential candidates, focusing on the modality of stimulus presentation, emotion category and individual baseline hormone levels. In an additional exploratory analysis, we examined the association of testosterone x cortisol interaction with recognition accuracy and reaction times. We obtained accuracy and reaction time scores from 282 males who categorized voice, face and voice-face stimuli for nonverbal emotional content. Results showed that recognition accuracy was significantly higher in the audio-visual than in the auditory or visual modality. While Spearman's rank correlations showed no significant association of testosterone (T) with recognition accuracy or with response times for specific emotions, the logistic and linear regression models uncovered some evidence for a positive association between T and recognition accuracy as well as between cortisol (C) and reaction time. In addition, the overall effect size of T by C interaction with recognition accuracy and reaction time was significant, but small. Our results establish that audio-visual congruent stimuli enhance recognition accuracy and provide novel empirical support by showing that the interaction of testosterone and cortisol relates to males' accuracy and response times in emotion recognition tasks.